A Matched Case-Control Study on Open and Endovascular Treatment of Popliteal Artery Aneurysms. (September 2018) - Dorigo, W.; Fargion, A.; Masciello, F.; Piffaretti, G.; Pratesi, G.; Giacomelli, E.; Pratesi, C.
Objective: To compare early and late results of open and endovascular management of popliteal artery aneurysm in a retrospective single-center matched case-control study Methods: From 1981 to 2015, 309 consecutive interventions for popliteal artery aneurysm were performed in our institution, in 59 cases with endovascular repair and in 250 cases with open repair. Endovascular repair was preferred in older asymptomatic patients, while open repair was offered more frequently to patients with a thrombosed popliteal artery aneurysm and a poor run-off status. A one-to-one coarsened exact matching on the basis of the baseline demographic, clinical, and anatomical covariates significantly different between the two treatment options was performed and two equivalent groups of 56 endovascular repairs and open repairs were generated. The two groups were compared in terms of perioperative results with χ 2 test and of follow-up outcomes with the Kaplan–Meier curves and log-rank test. Results: There were no differences between the two groups in terms of perioperative outcomes. Median duration of follow-up was 38 months. Five-year survival rates were 94% in endovascular repair group and 89.5% in open repair group (p = 0.4, log-rank 0.6). Primary patency rates at 1, 3, and 5 years were 81%, 78%, and 72% in endovascular repair group and 82.5%, 80%, and 64% in open repair group (p = 0.8, log-rank 0.01). Freedom from reintervention at 5 years was 65.5% in endovascular repair group and 76% in open repair group (p = 0.2, log-rank 1.2). Secondary patency at 1, 3, and 5 years was 94%, 86%, and 74% in endovascular repair group, and 94%, 89%, and 71% in open repair group, respectively (p = 0.9, log-rank 0.01). The rates of limb preservation at 5 years were 94% in endovascular repair group and 86.4% in open repair group (p = 0.3, log-rank 0.8). Conclusion: Open repair and endovascular repair of popliteal artery aneurysms provided in this retrospective single-center experience similar perioperative and follow-up results in equivalent groups of patients.